Untargeted and targeted mass spectrometry reveal the effects of theanine on the central and peripheral metabolomics of chronic unpredictable mild stress-induced depression in juvenile rats - Yanru Zhu; Feng Wang; Jiatong Han; Yunli Zhao; Miao Yu; Mingyan Ma; Zhiguo Yu (Elsevier, 2023)
l-theanine has been shown to have a therapeutic effect on depression. However, whether l-theanine has an excellent preventive effect on depression in children and adolescents and what its mechanism is have not been well explained. Given the complexity of the pathogenesis of depression, this study investigated the preventive effect and mechanism of l-theanine on depression in juvenile rats by combining serum and hippocampal metabolomic strategies. Behavioral tests, hippocampal tissue sections, and serum and hippocampal biochemical indexes were studied, and the results confirmed the preventive effect of l-theanine. Untargeted reversed-phase liquid chromatography-quadrupole-time-of-flight mass spectrometry and targeted hydrophilic interaction liquid chromatography-triple quadrupole mass spectrometry were developed to analyze the metabolism changes in the serum and hippocampus to screen for potential biomarkers related to l-theanine treatment. The results suggested that 28 abnormal metabolites in the serum and hippocampus that were considered as potential biomarkers returned to near-normal levels after l-theanine administration. These biomarkers were involved in various metabolic pathways, mainly including amino acid metabolism and lipid metabolism. The levels of amino acids and neurotransmitters in the phenylalanine, tryptophan, and glutamic acid pathways were significantly reduced after l-theanine administration compared with chronic unpredictable mild stress-induced rats. In summary, l-theanine had a significant preventive effect on depression and achieved its preventive results on depression by regulating various aspects of the body, such as amino acids, lipids, and inflammation. This research systematically analyzed the mechanism of l-theanine in preventing depression and laid the foundation for applying l-theanine to prevent depression in children and adolescents.